Peran Program Buruan Sae Dalam Membangun Civic Ecology Berbasis Karakter Ramah Lingkungan pada Masyarakat Kota Bandung - Nurjaenudin, Ripal Ilham; Fitriasari, Susan; Fitria, Ratna (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Public environmental awareness is a serious challenge in realizing a sustainable city. In addressing this issue, the City of Bandung launched the Buruan SAE Program which aims to utilize yard land through household-based urban farming practices. This research is motivated by the need for a citizen-based approach in building civic ecology, namely a socio-ecological practice that integrates citizenship values and responsibility towards the environment. The purpose of this study is to examine how the Buruan SAE Program contributes to fostering environmentally friendly character among residents and strengthening civic ecology in the City of Bandung. Data collection techniques were carried out through the stages of observation, interviews and documentation studies from relevant sources. This program can be a great potential for replication in other urban areas as a model of community empowerment based on civic ecology and sustainable environmental character development.